Physician perspectives on the burden and management of asthma in six countries: The Global Asthma Physician Survey (GAPS). Issue 1 (December 2017) - Chapman, Kenneth; Hinds, David; Piazza, Peter; Raherison, Chantal; Gibbs, Michael; Greulich, Timm; Gaalswyk, Kenneth; Lin, Jiangtao; Adachi, Mitsuru; Davis, Kourtney
Abstract Background Despite recognition of asthma as a growing global issue and development of global guidelines, asthma treatment practices vary between countries. Several studies have reported patients' perspectives on asthma control. This study presents physicians' perspectives and strategies for asthma management. Methods Physicians seeing ≥4 adult patients with asthma per month in Australia, Canada, China, France, Germany, and Japan were surveyed (N =1809; ≈300 per country). A standardised questionnaire was developed for this study and administered by telephone, online or face-to-face. Statistics were weighted to account for the sampling scheme. Results Physicians estimated that 71% of their adult patients received maintenance medication, with adherence monitored by 76–97% of physicians. Perceived major barriers to patient adherence included: patients taking treatment as needed; acceptance of symptoms; and patients not perceiving treatment benefits. Written action plans (37%) and technology (15%) were seldom employed by physicians to aid patients' asthma management. Physicians rarely (10%) used validated patient-reported questionnaires to monitor asthma control, instead monitoring selected symptoms, exacerbations, and/or lung function measurements. Awareness of single maintenance and reliever therapy (SMART/MART) varied among countries (56–100%); although most physicians (72%) had prescribed SMART/MART, the majority (91%) co-prescribed a short-acting bronchodilator at least some of the time. Conclusions These results show that physicians generally do not employ standardised tools to monitor asthma control or to manage its treatment and that despite high awareness of SMART/MART, the strategy appears to be commonly misapplied. Better education for patients and physicians is required to improve asthma management and resulting patient outcomes.